Pelatihan Metode Meditasi Lectio Divina Bagi Pencak Silat Katolik THS-THM - Panda, Herman; Taso, Donatus Bhato; Gawo, Ferdinandus Ovan; Minggu, Arkadius; Ukat, Arnoldus Jansen; Wudi, Aloysius; Lau, Estevanus Lau; Sambi, Desidarius; Ikun, Sekundus; Ate, Fransiskus Tena; Deta, Vinsensius Pote (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The Catholic Pencak Silat Tunggal Hati Seminari – Tunggal Hati Maria (THS-THM) is a self-defense training club that serves as a platform for fostering faith and character development among young Indonesian Catholics. Established in Jakarta in 1985, this organization's commitment to cultivating faith and character has extended to numerous dioceses across Indonesia. Functioning as a nurturing space for faith, THS-THM has traditionally drawn inspiration from the Holy Scripture since its inception. However, over time, some local branches at the grassroots level have shifted their focus towards breathing meditation, departing from the traditional reliance on the Holy Scripture. This service activity aims to introduce and train THS-THM members in the distinctive Catholic meditation method of Lectio Divina, emphasizing a connection with the Holy Scripture. The Lectio Divina method comprises four main steps: lectio (reading), meditatio (meditation), oratio (prayer), and contemplatio (contemplation). Through this approach, THS-THM members can attain a profound understanding of their faith and undergo character formation deeply rooted in the Holy Scripture.The implementation of this method involves lectures, question-and-answer sessions, and the sharing of personal experiences. The outcomes of this activity are twofold: firstly, an increased awareness among THS-THM members regarding the significance of the Holy Scripture as a source of spirituality and character development. Secondly, enhancement in the participants' proficiency in practicing the Lectio Divina meditation method.